(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Indian English novelists have chronicled the history,socio-political consciousness, changing culture and traditions andsocio-economic concerns of India, in the colonial, post-colonial andpost-independence eras. While national events occupy centre-stage in somenovels, they are merely used as a backdrop in others. At times, it isimpossible to separate the fictional element from contemporary nationalhistory. The interaction between national events and private lives, asreflected in the Indian English novel, makes for a stimulating study. In thiscontext, this thesis focuses on how the life and destiny of the individual andthe life and destiny of the nation-state in post-independence India, arepresented as being intertwined, in select Indian English novels.